Komunikasi Interpersonal Orang Tua Dalam Pembinaan Perilaku Anak Di Kelurahan Klaru Distrik Mariat Kabupaten Sorong - Wahidi, A.R.; Hamzah, Hamzah (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2022)
This study aims to get an overview of interpersonal communication relationships and the role of parents' interpersonal communication in fostering children's behavior in the Klaru village, Mariat district, Sorong regency. This research uses a type of qualitative research with a descriptive approach. Data was collected using data collection techniques in the form of interviews which were then analyzed using data reduction analysis techniques, data presentation and conclusion. The results show that the process of interpersonal communication in the Klaru sub-district creates openness between children and parents, parents make themselves good friends for their children, parents become good listeners for their children, creates a sense of mutual respect, creates a sense of care and affection, creates a sense of children's self-confidence, creating space for children to express their feelings. The role of good interpersonal communication must be carried out by parents by prioritizing the interests of the child, and interactions that occur not only from parent to child, but also between child and parent. From the communication that exists, parents are able to guide their children to behave well, such as speaking polite and polite words, nurturing children to develop a sense of faith and love for Allah SWT, fostering children to have a sense of responsibility, discipline and independence. Fostering children in worship, nurturing children to have good moral behavior, nurturing children with gentleness, nurturing children by following the example of the Prophet Muhammad SAW, nurturing children by giving advice. In fostering children's behavior, of course parents need to cooperate well and patience is needed in fostering children